HUBUNGAN TINGKAT PENGETAHUAN TENTANG DAMPAK KEHAMILAN PADA USIA REMAJA DENGAN SIKAP REMAJA PUTRI TERHADAP PENCEGAHAN KEHAMILAN USIA REMAJA - Narti Bora; Anik Sri Purwanti (Journal of Innovative and Creativity (Joecy), 2026)
Adolescent pregnancy remains a significant reproductive health concern because of its physical, psychological, social, and economic consequences. Improving adolescents’ knowledge of these consequences is expected to encourage positive attitudes toward preventing early pregnancy. This study investigated the relationship between adolescent girls’ knowledge and attitudes regarding the impacts of adolescent pregnancy. A quantitative cross-sectional design was employed involving 30 girls aged 12–17 years selected through simple random sampling. Knowledge and attitudes were measured using structured questionnaires and analyzed with the Spearman Rank correlation test (p<0.05). Most participants demonstrated good knowledge (46.7%) and positive attitudes (60.0%). Statistical analysis revealed a significant positive relationship between knowledge and attitudes (p=0.001; r=0.612), indicating that higher knowledge was associated with more favorable attitudes toward preventing adolescent pregnancy. These findings highlight the importance of strengthening reproductive health education through schools, families, and healthcare providers to improve adolescents’ knowledge and foster positive attitudes toward maintaining reproductive health.